Caracterização e relações entre caracteres agronômicos de milho e bromatológicos da silagem no sudoeste do Paraná - Carvalho, Acir Felipe Grolli (2013)
The objective of this study was to characterize the corn silages of different genotypes and to examine relationships between agronomic and chemical characteristics of corn silage in southwestern Paraná. So the experiment was conducted in farm of Universidade Tecnológica Federal do Paraná (UTFPR), Campus Dois Vizinhos in two years (2009/2010 and 2010/2011). In both years of experiments, maize seeds were supplied by Embrapa Milho e Sorgo (Sete Lagoas, MG) and are part of field trials of maize genotypes in Brazil representing the cycle test early. For the two years of the experiment experimental design used was lattice with 49 treatments (2009/10) and alpha lattice design with 39 treatments (2010/11) both with two replications. The chemical characteristics evaluated were: dry matter, ash, ether extract, crude protein, neutral detergent fiber, acid detergent fiber, net energy of lactation and total digestible nutrients. The agronomic traits were as follows: dry matter yield, percentage of stems, green leaves and spike against corn plant, stem diameter, ear length, ear diameter, cob weight, grain number in row, number of rows, number of days to flowering and total grain production. The results of the observed variables were subjected to analysis of variance and the characteristics that showed significative differences were compared by SNK, at the 5% level of significance, using the statistical software Genes. Pearson correlation coefficients between morphological and qualitative characteristics were estimated the diagnosis of multicollinearity. Then the remaining correlations between traits were deployed in direct and indirect effects achieved through path analysis, was used to assist in the software GENES analysis of variance and track. These procedures were repeated in both experiments. There were significant positive and negative correlations with direct and indirect effects between the chemical characteristics of dry matter production per hectare, crude protein and net energy of lactation with agronomic characteristics of corn plant. The qualitative characteristics should be increasingly used for the selection of materials for the production of silage, especially the quality of the fiber.